Front Cover: Proteomic and Post‐Translational Modification Profiling of Exosome‐Mimetic Nanovesicles Compared to Exosomes. Issue 8 (16th April 2019) - Nasiri Kenari, Amirmohammad; Kastaniegaard, Kenneth; Greening, David W.; Shambrook, Mitch; Stensballe, Allan; Cheng, Lesley; Hill, Andrew F.
Abstract : DOI:10.1002/pmic.201800161 Proteomic profiling of mimetic‐nanovesicles (M‐NVs) generated from cells reveals a subset of proteins that are highly abundant in M‐NVs. M‐NVs are found to contain proteins associated with membrane and cytosolic components that largely represent the parental cell proteome, whereas the profile of exosomes highlights their endosomally derived origin. In article number1800161, Nasiri Kenari et al. demonstrate the potential advantage of M‐NVs as an alternative nanocarrier when spontaneous endosomal sorting of therapeutics is limited.